The Prevention of Spontaneous Combustion in the South Durham Area - R. L. Robinson; C. Scott; W. R. Donaghue (The Institute of Materials, Minerals and Mining, 1905)
Whilst spontaneous combustion has never been considered a major problem in south Durham, certain collieries in the area have a history of heatings and precautions are essential. Three collieries are affected - Shotton, Vane Tempest and Seaham - and in the case of the last two, there are huge areas of high quality coal to work under conditions where spontaneous combustion is a real hazard. The seam being extracted has an immediate roof in goaf left by the incomplete extraction of a contiguous seam worked before the turn of the century. The presence of residual coal stocks and old roadways and cavities adds to the difficulty of preventing unwanted air movement. The main preventive measures adopted are the construction of airtight gateside packs and the use of sprayed surface coatings in the gate. Sampling systems and sampling points are described and, in particular the field of continuous monitoring from the surface is examined. The resulting possibility of a quantitative as well as qualitative assessment of the preventative measures required is discussed.